#TITLE_ALTERNATIVE# - Haetami (NIM 20595505), Aceng
ABSTRACT: Reverse osmosis (RO) membranes have been prepared by varied compositions of cellulose acetate (CA), polyvinyl pyrrolidone (PVP), and L4-dioxan (Diox). Those membranes were prepared by phase inversion technique. These membranes were then used for RO process of aluminium waste water which contains Fe and Al ions. These processes were done with applied pressure of 5, 15, and 25 atm. The results showed that higher concentration of PVP resulted in higher permeability, lower selectivity, and higher swelling degree. Membrane permeability and selectivity could also be increased by using higher applied pressure. The bursting strength testing showed a decrease of membrane mechanical properties after the RO process. This could be explained by the deformation and widening of membrane pores. The optimum results have been obtained by using a membrane composition of 20% CA, 5% PVP, and 75% Diox , i.e. a flux of 18.91 L/m2h, 97.03% rejection of Al ions and 98.21% rejection of Fe ions with an applied pressure of 25.